Efektivitas Madu Murni dan Propolis Terhadap Bakteri Pencemar Susu Penyebab Foodborne Disease pada Produk Susu Kemasan - Fidati Hanifa; Ratna Purwaningrum; Festy Ladyani Mustofa; Zulfian Zulfian (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Milk is nutritious food, but it is easily contaminated with bacteria. Bacteria-contaminated milk if it consumed can cause foodborne disease. One of the functions of foodborne is antibiotic, however, the usage of the antibiotic synthesis needs to focus more to prevent the resistance. Pure honey and propolis are the natural substances that are believed to have an antibiotic effect. Purpose: The purpose of this research is to know the effectiveness of pure honey and propolis towards milk pollutant bacteria caused by foodborne disease in packaged milk products. Research Method: This research is using an experimental research method. Data obtained descriptively and qualitatively. The result: Pure honey with 100% concentration has an average diameter of obstacles zone 16.75 mm. Propolis with 100% concentration has an average diameter of obstacles zone 20.25 mm. Conclusion: The effectiveness of propolis towards milk pollutant bacteria caused foodborne disease in packaged milk products which has an average diameter of obstacles zone 20.25 mm, the effectiveness of pure honey towards milk pollutant bacteria caused foodborne disease in packaged milk products which has an average diameter of obstacles zone 16.75 mm.